Coupling of indigenous-patient-friendly cultural communications with clinical care guidelines for type 2 diabetes mellitus - Forbes, David; Sidhu, Amandeep; Singh, Jaipal (Australia Computer Society, 2011)
Distance, terrain, climate and inadequate medical resources seriously constrain health care accessibility for rural and remote Indigenous communities of Western Australia (WA). Management of the Type 2 Diabetes Mellitus (T2DM), a chronic condition affecting Indigenous people much more than non-Indigenous, requires a complex assortment of time-sensitive communications activity and interventions to avert serious complications. Communications barriers arising from pervasive cultural misunderstanding in primary care go far beyond language differences and routine translation techniques. Practitioners and patients lacking the capability and capacity to facilitate dialogue for shared meaning in the examination and testing discourse need a culturally sensitive purpose-driven informatics system of support for the Patient-Practitioner Interview Encounter (PPIE). The dominant unidirectional clinician-biased forms of communication employed by healthcare professionals are a major barrier. Our developing communications support model utilizes the mapping of ontologies. The Community Healthcare ontology is dedicated to mapping a clinical taxonomy for T2DM national guidelines to Aboriginal English (AE). The eventual user interface will represent Aboriginal patient-culture-driven access to and use of interactive audio visual media in the primary healthcare setting.This research objective establishes value of and respect for the Aboriginal patient’s dialectal and pragmatic preferences, thereby enabling us to couple these preferences with Australia’s Standard English clinical communications practice in the treatment and care of IndigenousT2DM patients. A critical capability of the eventual application, especially when phrase ontology guidance enters the interface will be the interception of ambiguities and mitigation of misinterpretation risk. The emphasis is concentrated on bi-directional communications assistance that will not only enhance the Aboriginal patient opportunity to contribute to the PPIE, but will reinforce the value of and reciprocal respect for, sound clinical practice.